A rare grade III symptomatic Tsunoda class III left lobe hepatolithiasis in a North American woman. (30th October 2012) - Abu-Wasel, Bassam; Keough, Valerie; Molinari, Michele
Abstract : A 44-year-old Caucasian woman without any identified predisposing factors, presented to her local emergency room with multiple episodes of recurrent ascending cholangitis. She underwent a laparoscopic cholecystectomy several years prior to her admission to the hospital for parenteral antibiotic therapy and she had no personal or family history of hypercholesterolaemia. Transferred to a tertiary hospital for surgical therapy, she underwent a left hepatic resection for a chronically infected left lobe hepatolithiasis (HL) conditioning atrophy of the parenchyma due to obstruction of the biliary tree by multiple large cholesterol stones. HL is a very rare condition in Western countries and its aetiology and predisposing factors are still unclear. We present her symptomatology, diagnostic and therapeutic management and discuss the epidemiology and risk factors of HL, that is, a common condition in South East Asia while exceptional in Caucasian patients who have not travelled in high-prevalence regions.